ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Editorial. - Jacke, Christoph; Autsch, Sabine; Pickartz, Tim (Impulse. Texte und Bilder zur Kunstvermittlung.)

On the Integration of Sampling Rate Synchronization and Acoustic Beamforming - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))

Nietzsche’s Search for Philosophy: On the Middle Writings Keith Ansell-Pearson - Corall, Niklas (The Agonist)
In Nietzsche’s Search for Philosophy – On the Middle Writings, Keith Ansell Pearson directs his interpretive gaze to the middle writings of Nietzsche’s oeuvre, namely Human, All Too Human (HAH), Dawn and The Gay Science (GS). While at least in German Nietzsche scholarship, it is rather debatable whether or not the middle writings should have been considered “neglected”– with perhaps Dawn being a reasonable exception – it is important to read them as more than merely a detour from the “real Nietzsche” found in the Birth of Tragedy and then the late works. While Ansell-Pearson does not presume a homogeneous philosophical approach in the middle works, he characterizes the period as a whole and each work in itself as containing important aspects of Nietzsche’s “search for philosophy”, especially in consideration of Nietzsche’s attempts to “unify thought and life” (4) in what is labelled a “‘philosophical life’” (4).
Keywords: Ocean Engineering

Digitale Bruchstücke zwischen Faktalismus und Zukunftsnarration: Der Letzte Mensch und Algorithmische Regime - Corall, Niklas (Nietzsche, die Medien und die Künste im Zeitalter der Digitalisierung)

Digitizing Processes in Manufacturing Companies via Low-Code Software (to appear) - Weidmann, Nils; Kirchhoff, Jonas; Sauer, Stefan
Low-code development platforms (LCDPs) recently sparked interest in both academia and industry, promising to speed up software development and make it accessible to users with little or no programming experience. Thus, the mass-development of software applications that are custom-made to the tasks, skills, and preferences of end users is potentially enabled. Although different LCDPs have been analysed with respect to their functionality and applied to exemplary case studies in recent work, there is a shortage of experience reports in which LCDPs are used to digitize business processes in small and medium manufacturing enterprises. In this paper, we therefore summarize our experience from supporting industry partners to identify business processes that are suitable for being implemented with low-code technologies and to select an LCDP that meets the requirements of the business process while aligning with the overall digitization strategy of the respective company. We also present the opportunities and challenges of the low-code approach as perceived by industry partners. In summary, the low-code approach should be seen as an essential factor for the digitization of business processes in small and medium manufacturing companies.

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Creativity in entrepreneurship: Dancing between nothing and structure - Hubner-Benz, Sylvia; Frese, Michael (Handbook of Organizational Creativity)

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, A.; Singh, Amit; Banh, Ngoc Chi; Richter, B.; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, B. (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: HRI; XAI; negation; understanding; explaining; touch interaction; gesture

Tod mit Kindern thematisieren - Magdeburg, Lena Maria (Grundschule)

Medienpädagogische Professionalisierung in der beruflichen Weiterbildung. Eine Studie aus Perspektive der biografischen Medienforschung - Dehmel, Lukas

A new approach to model the fluid dynamics in sandwich packings - Franke, Patrick; Shabanilemraski, Iman; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Product and Process Modeling)
Abstract Sandwich packings represent new separation column internals, with a potential to intensify mass transfer. They comprise two conventional structured packings with different specific geometrical surface areas. In this work, the complex fluid dynamics in sandwich packings is modeled using a novel approach based on a one-dimensional, steady momentum balance of the liquid and gas phases. The interactions between the three present phases (gas, liquid, and solid) are considered by closures incorporated into the momentum balance. The formulation of these closures is derived from two fluid-dynamic analogies for the film and froth flow patterns. The adjustable parameters in the closures are regressed for the film flow using dry pressure drop measurements and liquid hold-up data in trickle flow conditions. For the froth flow, the tuning parameters are fitted to overall pressure drop measurements and local liquid hold-up data acquired from ultra-fast X-ray tomography (UFXCT). The model predicts liquid hold-up and pressure drop data with an average relative deviation of 16.4 % and 19 %, respectively. Compared to previous fluid dynamic models for sandwich packings, the number of adjustable parameters could be reduced while maintaining comparable accuracy.
Keywords: Modeling and Simulation; General Chemical Engineering

When Did Europe Become Identified With Christianity? The Revolutionary Origins of an All Too Common Slogan - Süßmann, Johannes (Beyond Binaries. Religious Diversity in Europe)

Korpora für Deutsch als Fremdsprache – Potenziale und Perspektiven - Weber, Tassja; Flinz, Carolina; Mell, Ruth; Möhrs, Christine (Korpusgestützte Sprachanalyse. Grundlagen, Anwendungen und Analysen)

Novel Cascaded Incremental Nonlinear Dynamic Inversion Controller Approach for a Tiltrotor VTOL - Henkenjohann, Mark; Nolte, Udo; Henke, Christian; Trächtler, Ansgar (2023 International Conference on Unmanned Aircraft Systems (ICUAS))

Controlled Rivet Deformation During Self-piercing Riveting Through a Tailored Strength Distribution Within the Rivet Material - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity.)

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.

Intrinsic forming of hybrid parts made of laser-structured aluminium sheet and CFRP-Prepreg - Wu, Shuang; Freund, Jonathan; Delp, Alexander; Haubrich, Jan; Löbbecke, Miriam; Walther, Frank; Tröster, Thomas

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Modellierung der axialen Dispersion in Struktur- und Anstaupackungen - Franke, Patrick; Shabanilemraski, Iman; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y.

Autonomous Golf Putting with Data-Driven and Physics-Based Methods - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (2022 Sixth IEEE International Conference on Robotic Computing (IRC))

Verfahren zum Betreiben einer elektrooptischen Übertragungsvorrichtung für beliebige Signale, Computerprogrammprodukt sowie Datenübertragungsvorrichtung - Kruse, Stephan; Scheytt, J. Christoph; Meinecke, Marc-Michael; Heiko Gustav, Kurz
Die Erfindung betrifft ein Verfahren zum Betreiben einer elektrooptischen Übertragungsvorrichtung, mit den Schritten: - Erzeugen eines optischen Trägersignals mittels einer optischen Signalquelle einer Basiseinrichtung der Übertragungsvorrichtung; - Erzeugen eines beliebigen Signals mittels der optischen Signalquelle; - Aufmodulieren des beliebigen Signals auf das optische Trägersignal in der Basiseinrichtung zu einem Übertragungssignal; - Übertragen des Übertragungssignals an eine Antenneneinrichtung der Übertragungsvorrichtung mittels eines optischen Übertragungsmediums; und - Trennen des beliebiges Signals und des Trägersignals in der Antenneneinrichtung. Ferner betrifft die Erfindung ein Computerprogrammprodukt sowie eine Übertragungsvorrichtung.

Einstellbare Signalquelle mit kleinem Phasenrauschen - Bahmanian, Meysam; Scheytt, J. Christoph
Die Erfindung betrifft eine einstellbare Signalquelle mit kleinem Phasenrauschen, aufweisend • einen optischen Mikrowellenphasendetektor (BOMPD) aufweisend • einen Intensitätsmodulator (BIM), mit einem optischen Signaleingang, einem Modulationseingang (I), und einem ersten Ausgang (O1) und einen zweiten Ausgang (O2), • eine erste Photodiode (PD1), die im Betrieb mit Licht des ersten Ausgangs (O1) bestrahlt werden kann, • eine zweite Photodiode (PD2), die im Betrieb mit Licht des zweiten Ausgangs (O2) bestahlt werden kann, • wobei die erste Photodiode (PD1) und die zweite Photodiode (PD2), im Betrieb vorgespannt in Reihe geschaltet sind, • wobei zwischen der ersten Photodiode (PD1) und der zweiten Photodiode (PD2) ein Abgriff für eine Abgriffs-Signal angeordnet ist, • weiterhin aufweisend eine steuerbare Gleichstromquelle, • wobei am Abgriff im Betrieb mittels der ersten Gleichstromquelle (N4) ein Offsetstrom einstellbar ist, womit die Symmetrie des optischen Mikrowellenphasendetektor im Betrieb durch einen Offsetstrom aufgehoben wird, • wobei der Abgriff mit einem eventuellen Offsetstrom an ein Tiefpassfilter geführt wird, • wobei das tiefpassgefilterte Abgriffs-Signal einem einstellbaren Oszillator (OSZ) zur Verfügung gestellt wird.

Softsensor model of phase transformation during flow forming of metastable austenitic steel AISI 304L - Rozo Vasquez, Julian; Arian, Bahman; Kersting, Lukas; Walther, Frank; Homberg, Werner; Trächtler, Ansgar

Hybrid Optimal Control for Dynamical Systems using Gaussian Process Regression and Unscented Transform* - Hesse, Michael; Timmermann, Julia; Trächtler, Ansgar (2023 European Control Conference (ECC))

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Case Study III: Challenges of lightweight design, vehicles, and rescuers - Akbulut Irmak, Emine Fulya; Hanses, Hendrik; Horwath, Ilona; Tröster, Thomas (Climate Protection, Resource Efficiency, and Sustainable Engineering)

Introduction to the Minitrack on Data-driven Services in Manufacturing: Innovation, Engineering, Transformation, and Management - Koldewey, Christian; Martin, Rabe; Dumitrescu, Roman; Winter, Johannes (Proceedings of the 56th Hawaii International Conference on System Sciences)

Datengestützte Produktplanung
Unter dem Einfluss der Digitalisierung wandeln sich mechatronische Produkte zunehmend in cyber-physische Systeme (CPS). Diese sind in der Lage, umfangreiche Daten während ihres Betriebs zu sammeln und über digitale Netzinfrastrukturen zur Verfügung zu stellen. Gemeinsam mit weiteren Daten aus der Betriebsphase versprechen sie wertvolle Erkenntnisse über das Produkt und dessen Nutzer, welche für die Hersteller der CPS insbesondere für die Planung zukünftiger Produktgenerationenrelevant sind. Die zielgerichtete Nutzung von Betriebsdaten in der strategischen Produktplanung stellt produzierende Unternehmen jedoch noch vor zahlreiche Herausforderungen, z. B. hinsichtlich der Identifizierung Erfolg versprechender Use Cases. Das vorliegende Buch greift diese Herausforderungen auf und stellt ein Instrumentarium vor, das produzierende Unternehmen zur datengestützten Produktplanung befähigt. Neben der Vorstellung praxiserprobter Methoden und Werkzeuge werden Einblicke in vier Pilotprojekte gegeben. Das Instrumentarium entstand im Forschungsprojekt „DizRuPt“, das vom Bundesministerium für Bildung und Forschung (BMBF) gefördert wurde.

Evaluation of the effects of different heating strategies on the joining partners during infrared welding of black polyamides - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J.

Evaluation of Infrared Welded Joints of Short Fiber Reinforced Thermoplastics Using Digital Image Correlation - Schöppner, Volker; Gevers, Karina; Schraa, L.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Proceedings of the 2023 International Conference on Composite Materials)

Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen (QSS) von Thermoplasten - Schöppner, Volker; Arndt, Theresa (Joining Plastics)

Dielectric Heating in the Vulcanization Process of Rubber Extrudates - Schöppner, Volker; Petzke, J.

Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Conjunctive and additive group work reduce academic procrastination: insights from a vignette study - Koppenborg, Markus; Klingsieck, Katrin B.; Hüffmeier, Joachim (Current Psychology)
Abstract Group work can increase individual effort, performance, and positive affect, if group members perceive their own contribution as indispensable for the group product. A vignette methodology was applied to investigate whether group work may also reduce procrastination. The vignettes described a typical academic assignment, while varying the task structure (individual work vs. conjunctive group work vs. additive group work) and group member ability (high vs. low). For each vignette, student participants ( N = 443) provided ratings on their perceived indispensability, procrastination of the assignment, and affect. When group member ability was high, procrastination was lower in additive group work as compared to individual work. When group member ability was low, procrastination was lower in conjunctive group work as compared to both individual work and additive group work. As predicted, perceived indispensability mediated the difference in procrastination between conjunctive and additive group work. Moderation analyses further revealed that the effects were more pronounced for high trait procrastinators. Further, both types of group work led to increases in task-related positive affect as compared to individual work. By demonstrating the relevance of group work as a social factor, the results should be useful for the extension of existing programs targeting procrastination, and may inspire measures for preventing procrastination by changes in the study environment.
Keywords: General Psychology

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science

Nächstes Jahr in Jerusalem – oder auch nicht. Perspektiven auf Deutschland und Israel in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" und Mirna Funks "Winternähe" - Spener, Anna Maria (DINGS 2021. Beiträge zur Digitalen INternationalen Germanistischen Studierendentagung. Literatur des 20. und 21. Jahrhunderts)

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice—A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Feedback processing in cognitive and motor tasks: A meta‐analysis on the feedback‐related negativity - Faßbender, Laura; Krause, Daniel; Weigelt, Matthias (Psychophysiology)
Abstract For motor learning, the processing of behavioral outcomes is of high significance. The feedback‐related negativity (FRN) is an event‐related potential, which is often described as a correlate of the reward prediction error in reinforcement learning. The number of studies examining the FRN in motor tasks is increasing. This meta‐analysis summarizes the component in the motor domain and compares it to the cognitive domain. Therefore, a data set of a previous meta‐analysis in the cognitive domain that comprised 47 studies was reanalyzed and compared to additional 25 studies of the motor domain. Further, a moderator analysis for the studies in the motor domain was conducted. The FRN amplitude was higher in the motor domain than in the cognitive domain. This might be related to a higher task complexity and a higher feedback ambiguity of motor tasks. The FRN latency was shorter in the motor domain than in the cognitive domain. Given that sensory information can be used as an external feedback predictor prior to the presentation of the final feedback, reward processing in the motor domain may have been faster and reduced the FRN latency. The moderator variable analysis revealed that the feedback modality influenced the FRN latency, with shorter FRN latencies after bimodal than after visual feedback. Processing of outcome feedback seems to share basic principles in both domains; however, differences exist and should be considered in FRN studies. Future research is motivated to scrutinize the effects of bimodal feedback and other moderators within the motor domain.
Keywords: Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; Biological Psychiatry; Cognitive Neuroscience; Developmental Neuroscience; Endocrine and Autonomic Systems; Neurology; Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; General Neuroscience

Imagine to automatize: automatization of stimulus–response coupling after action imagery practice in implicit sequence learning - Dahm, Stephan F.; Hyna, Henri; Krause, Daniel (Psychological Research)
Abstract Action imagery practice (AIP) describes the repetitive imagination of an action to improve subsequent action execution. Because AIP and action execution practice (AEP) draw on partly similar motor mechanisms, it was assumed that AIP may lead to motor automatization, which is observable in a reduction of dual-task costs after AEP. To investigate automatization in AIP, we compared dual-task and single-task performance in practice and random sequences in pretests and posttests. All participants practiced serial reactions to visual stimuli in ten single-task practice sessions. An AIP group imagined the reactions. An AEP group and a control practice group executed the reactions. Practice followed a sequential sequence in AIP and AEP but was random in control practice. In dual-task test conditions, tones were counted that appeared in addition to the visual stimuli. RTs decreased from pretest to posttest in both practice and random sequences in all groups indicating general sequence-unspecific learning. Further, RTs decreased to a greater extent in the practice sequence than in the random sequence after AIP and AEP, indicating sequence-specific learning. Dual-task costs—the difference between RTs after tone and no tone events—were reduced independent from the performed sequence in all groups indicating sequence-unspecific automatization. It is concluded that the stimulus–response coupling can be automatized by both, AEP and AIP.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Auf Tuchfühlung mit dem Tod. - Brachtendorf, Charlotte

Aufschieben, weil man sich schlecht fühlt, oder sich schlecht fühlen, weil man aufschiebt? – Gruppenspezifische Unterschiede im Verhalten und Erleben von Prokrastination - Bobe, Julia; Klingsieck, Katrin B.

Prokrastination und das schlechte Gewissen - Gruppenunterschiede im Erleben und Auftreten von Prokrastination. - Bobe, Julia; Klingsieck, Katrin B.

Simulation of Infrared Welded Short Fiber Reinforced Thermoplastic Parts based on Mori-Tanaka Homogenization Method - Schöppner, Volker; Gevers, Karina; Hoenen, N.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Advanced Structured Materials)

Verbesserung der Betriebspunktauslegung durch Schneckensimulation - Schöppner, Volker; Austermeier, Laura; Trienens, Dorte (Wissenschaftlicher Arbeitskreis Kunststofftechnik)

The main factors influencing glass fiber shortening in the processing of bulk molding compounds (BMC) - Moritzer, Elmar; Scholle, Maximilian

Optimizing the Processing Performance of a Single Screw Extruder Using Live Simulations Based on Real Time Experimental Data - Köllermeier, Jonas; Schöppner, Volker

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

The Wave Must Be Right - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Plastic Insights)

Vorspannkraftrelaxation bei der Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian